Canadian Union Growth - Eastman, Byron (Relations industrielles / Industrial Relations, 1983)
This paper specifies a model of trade union membership growth in Canada. Because union growth affects and is affected by wage and price inflation, the model incorporates simultaneous equations with these three variables in endogeneous roles.